New record of the humpback whale (Megaptera novaeangliae) in the Adriatic Sea - Genov, Tilen (Annales. Series historia naturalis, 2009)
A report is submitted herein on the occurrence of a humpback whale in Slovenian territorial waters (Gulf of Trieste, North Adriatic Sea) during February, March and April 2009. This is a first confirmed and documented record of this species for Slovenia and the Gulf of Trieste...
Keywords: Adriatic Sea; Gulf of Trieste; Jadransko morje; kit grbavec; kiti; Megaptera novaeangliae; Slovenia; Slovenija; Tržaški zaliv